The Influence of Cost Volume Profit Analysis on Profit Planning at Private High Schools in Mataram City - Annisa Ramdani; Animah Animah (Citakonsultindo, 2024)
This research aims to determine the effect of cost-volume-profit analysis on profit planning in private high schools in Mataram City. The population of this study was in private final secondary schools in the city of Mataram. The number of samples in this study is based on data from the Mataram city deposit, namely 38 schools, using saturated sampling techniques. The data type used is quantitative data, which is primary data in a Likert scale questionnaire. Data processing techniques use the SPSS program. The data analysis method in this research uses multiple linear regression analysis. The research results show that cost-volume-profit analysis positively affects profit planning, and decision-making partially affects profits. Simultaneously, cost-volume profit analysis and decision-making positively affect profit planning. The results of this research have implications for schools, especially school principals, in making decisions and formulating policies regarding implementing cost-volume-profit analysis. School principals can use this analysis for special situations, such as decreased income due to not meeting the expected number of students. So, applying this analysis allows school principals to make more relevant decisions. That shows that using cost-volume-profit analysis and decision-making can increase profits at private high schools in Mataram City.